A nasal vaccine with inactivated whole-virion elicits protective mucosal immunity against SARS-CoV-2 in mice - Tokunoh, Nagisa; Tamiya, Shigeyuki; Watanabe, Masato; Okamoto, Toru; Anindita, Jessica; Tanaka, Hiroki; Ono, Chikako; Hirai, Toshiro; Akita, Hidetaka; Matsuura, Yoshiharu; Yoshioka, Yasuo (Frontiers in Immunology, 2023)
Vaccinations are ideal for reducing the severity of clinical manifestations and secondary complications of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2); however, SARS-CoV-2 continues to cause morbidity and mortality worldwide. In contrast to parenteral vaccines such as messenger RNA vaccines, nasal vaccines are expected to be more effective in preventing viral infections in the upper respiratory tract, the primary locus for viral infection and transmission. In this study, we examined the prospects of an inactivated whole-virion (WV) vaccine administered intranasally against SARS-CoV-2. Mice were immunized subcutaneously (subcutaneous vaccine) or intranasally (nasal vaccine) with the inactivated WV of SARS-CoV-2 as the antigen. The spike protein (S)-specific IgA level was found to be higher upon nasal vaccination than after subcutaneous vaccination. The level of S-specific IgG in the serum was also increased by the nasal vaccine, although it was lower than that induced by the subcutaneous vaccine. The nasal vaccine exhibited a stronger defense against viral invasion in the upper respiratory tract than the subcutaneous vaccine and unimmunized control; however, both subcutaneous and nasal vaccines provided protection in the lower respiratory tract. Furthermore, we found that intranasally administered inactivated WV elicited robust production of S-specific IgA in the nasal mucosa and IgG in the blood of mice previously vaccinated with messenger RNA encoding the S protein. Overall, these results suggest that a nasal vaccine containing inactivated WV can be a highly effective means of protection against SARS-CoV-2 infection.